Improved sound insulation in module based timber framed buildings - Ljunggren, Fredrik (Luleå tekniska universitet, Drift, underhåll och akustik, 2008)
This paper describes an ongoing research project at Luleå University of Technology. The project deals with lightweight building systems based upon industrial prefabricated building volumes. The size of each module can be approximately 8x4 m2. Although the technique has the same typical drawbacks as other similar lightweight building constructions, i.e. poor sound and vibration performance at low frequencies, the concept invites to some unique solutions which could benefit the sound properties. The overall objective of the project is to find new/modified economical constructions which enable module based wooden buildings to fulfill stated building codes with reasonable margin. Various constructions, and thereby various sound properties, should be offered according to the customers demand. The project contains a number of sub studies which are presented. Godkänd; 2008; Bibliografisk uppgift: USB; 20081215 (frel)